Monetary Policy, Growth and Employment in Developing Areas: A Review of the Literature - Pramod N. (Raja) Junankar (Institute of Labor Economics (IZA), 2019)
In this paper we review the literature on the impact that monetary policy has on growth and employment in developing countries. Much of the literature focusses on the impact of monetary policy on inflation levels and inflation volatility, and sometimes on output (GDP) levels and volatility of output. This survey of the literature on Monetary policy and growth shows that money plays a small role in developing countries and that monetary policy is not a very important influence on growth but may have some impact on inflation. Although there is much discussion about the merits of keeping inflation levels and volatility low, there is very little literature on studying the impact of low rates of steady inflation on the levels of private investment and technological change and hence on economic growth and on employment. There is very little research about the direct links between monetary policy and employment. The impact of growth on employment depends on what are the main drivers of economic growth and the initial state of the economy. Although growth may lead to increasing employment (formal and informal) there is little evidence showing that growth leads to an increase in "decent employment".
Keywords: E52; J4; O11; O17; O47; 330; monetary policy; role of money; growth; employment; development